P119 Responsiveness of the CAT (COPD Assessment Tool) in a stable and post exacerbation pulmonary rehabilitation population. (14th November 2013) - Chaplin, EJL; Chaplin, EJL; Gibb, M; Sewell, L; Singh, S; Singh, S
Abstract : Introduction: The CAT is an eight item questionnaire used to assess health status. It has previously been used in stable COPD and non COPD patients (Kon et al, 2012) and as an outcome measure for pulmonary rehabilitation (PR) in the short term in a stable population (Dodd et al, 2012). However the CAT has not been used in a post exacerbation rehabilitation programme. Aim: The aim of this study was to investigate whether there were any differences in response to the CAT between stable and post exacerbation patients undertaking rehabilitation. Methods: Patients attending a 7 week out patient PR programme were given a CAT questionnaire pre and post rehabilitation. Patients included were diagnosed with COPD and were either from the stable waiting list or patients who had been referred to PR following a hospital admission for exacerbation of COPD in the last 6 weeks. Results: 200 consecutive patients completed the CAT questionnaire -125 stable patients [74 male, MRC 3 (IQR 3–4), mean (SD) age 71.1 ( ± 8.9) years, FEV1 1.39L ( ± 0.6), BMI 28.5 ( ± 6.7)] and 75 post exacerbation patients [23 male, MRC 4 (IQR 3–5), mean (SD) age 70.6 ( ± 8.6) years, FEV1 1.16L ( ± 0.5), BMI 25.8 ( ± 7.3)]. There was a significant difference in baseline characteristics (BMI, FEV1 and MRC) between the groups ( p = 0.05). A statistically significant difference between the stable and post exacerbation patient groups CAT score pre rehabilitation (p = 0.05) was observed. However there was no significant difference in post rehabilitation CAT scores (p = 0.12) and the change in CAT scores between the 2 groups (p = 0.63). There was a significant difference between the groups' pre and post walking tests. The improvement in the ESWT (endurance shuttle walking test) in the stable group was greater (p< 0.05). Conclusion: Post exacerbation PR patients have a worse CAT score prior to PR when compared to a stable PR population but both groups make improvements in CAT following completion of PR.